Photocrosslinked Chitosan Hydrogels Reinforced with Chitosan‐Derived Nano‐Graphene Oxide. Issue 13 (31st May 2019) - Feng, Zhaoxuan; Hakkarainen, Minna; Grützmacher, Hansjörg; Chiappone, Annalisa; Sangermano, Marco
Abstract: Chitosan and chitosan‐derived nano‐graphene oxide carbon dots are successfully methacrylated and utilized for the fabrication of photocurable hydrogels. The addition of the nano‐graphene oxide (nGO) does not significantly delay the polymer network build‐up, but significantly reduces the storage modulus of the crosslinked network, with important detrimental effects on the mechanical performance. By replacing nGO with methacrylated M‐nGO, the mechanical performance of the crosslinked polymer network is improved with an increase of the storage modulus as a function of increasing the M‐nGO content in the photocurable formulation. Abstract : Chitosan and chitosan‐derived nano‐graphene oxide carbon dots (nGO) are successfully methacrylated and utilized for fabrication of photocurable hydrogels. Mechanical performances of chitosan‐based photocured hydrogels are given by dispersing methacrylated functionalized nGO.